Data algorithms and policies : redefining the digital world - Cimoli, Mario (UN ECLAC SantiagoCL, 2018)
Describes the fast-growing technological trajectories: the Internet of Things, blockchain and artificial intelligence. Analyses the two enablers of these technologies: global digital platforms and training for upgrading human resources to operate advanced digital technologies, drawing on recent data for seven Latin American countries; as well as the impact of these of other digital technologies in two vertical dimensions: manufacturing and advances services, and digital financial technology (fintech) firms.